Intensification of biodiesel synthesis from waste cooking oil (Palm Olein) in a Hydrodynamic Cavitation Reactor: Effect of operating parameters on methyl ester conversion - Chuah, L.F. (Elsevier, 2015)
This paper investigates a new route for intensification of methyl ester synthesis in Malaysia via alkali-catalysed transesterification of waste cooking oil derived from palm olein using a hydrodynamic cavitation reactor. The effects of the oil to methanol molar ratio (1:4-1:7), catalyst loading concentration (0.5-1.25wt) and reaction temperature (50-65Â°C) have been investigated using an optimised plate with 21 holes of 1mm diameter and an inlet pressure of 2bar in a 50L of hydrodynamic cavitation reactor assisted by a double diaphragm pump. Optimal conversion of 98.1 was achieved in 15min in a hydrodynamic cavitation reactor with 1:6 molar ratio of oil to methanol, 1wt of catalyst and 60Â°C of reaction temperature. It has been observed that a significant reduction in the optimum reaction time (about 6 fold) for transesterification from 90min for mechanical stirring approach to 15min for the hydrodynamic cavitation approach. Optimal yield efficiency of 12.50Ã10-4g/J was found using hydrodynamic cavitation and it was 8 fold higher than 1.5Ã10-4g/J when mechanical stirring was used. Â© 2015 Elsevier B.V.